Topical insulin and normal saline in chronic diabetic foot ulcers- A Prospective comparative study - Dayanand Biradar (Wolters Kluwer Medknow Publications, 2020)
Background: Diabetic foot ulcers are diabetes-related microvascular complications aggravated due to multiple pre-existing factors such as peripheral arterial disease, immune system factors, bone abnormalities, diabetic neuropathy, infections & repetitive external or minor trauma. Diabetic foot ulcers could lead to lower limb amputation if not managed appropriately. Studies have shown that insulin plays a vital role in wound healing. Objective: To evaluate the use of topical insulin in chronic diabetic foot ulcers at a tertiary care centre. Methods: A prospective study was conducted for a period of 12 months on 60 patients of the age group from 25-75 years who presented with diabetic foot ulcers were included. The subjects were divided into two groups, "group A" underwent dressing with topical insulin and group B underwent regular saline dressing. Sterile transparent gauze was used to measure the diameter). To calculate the wound area, these two diameters are multiplied to obtain an area in cm2. Ulcers were cleaned with normal saline and a sterile gauze soaked with Human mixtard insulin and normal saline 4 units 0.1 ml-Human mixtard insulin in 1 ml normal saline for each 10 cm2 of the wound in group A. Study data was analysed using SPSS software and Microsoft Excel software. Chi-square test was used to evaluate the results and P-value of <0.05 is considered significant. Results: Total of 60 patients were studied with Mean Age of 51.2 ± 9.6; 50.6 ± 10.9 years in group A & B respectively On day 0,7,15 wound measurements were done. A statistically significant difference was noted in the reduction of the average surface area of the wound at day 7, 15 between group A & B. insulin dressing group shown better changes than saline dressing group. Mean reduction in average surface area of the wound at day 15 was 67.8 ± 11.45 in insulin dressing group and 49.51 ± 18.21 in saline dressing group, statistically significant difference was noted. Average time required for granulation tissue to appear was 6.08 ± 2.15 days & 9.48 ± 4.21 days in group A & B respectively, statistically, a significant difference was noted (p< 0.001). Conclusion: The use of topical insulin is safe and effective in patients with diabetic foot ulcers. Topically applied insulin can accelerate wound healing without any systemic side effects.